A study on prevalence of dementia among elderly population in rural health training centre field practice area of Nalgonda - Balaraju, Ratna; Vallepalli, Chandrasekhar; Chandra Sekhar, K.; Prasad Sharma, M. M. V.; Sushmita, T. (International Journal Of Community Medicine And Public Health, 2020)
Background: Dementia is one of the major causes of disability and dependency among older people worldwide. Dementia has physical, psychological, social and economic impact. Worldwide prevalence of dementia in elderly population of more than 60 years is 5-8%. Prevalence of mild cognitive impairment in India is 14.89%. Present study aim was to estimate the prevalence of dementia and the risk factors associated with dementia among elderly population in rural field practice area of Nalgonda district. Methods: A descriptive, community based cross-sectional study was conducted among 119 elderly population in the field practice area of Rural Health Training Centre by simple random sampling method, with the help of a pre-designed and pre-tested questionnaire. Data was analyzed using SPSS Version 19. MMSE (mini mental status examination) questionnaire was used to screen for dementia. Barthel index was used to assess the dependency status. Results: Demographic profile of the study population of 119, males 65 (54.62%), females 54 (45.38%). Majority of their source of income were government service pension 30 (25.21%) and old age pension 70 (58.82%). 56 (47.06%) of elderly population living with family and 63 (52.94%) people were living individually. The study revealed the prevalence of cognitive impairment is 35.3%. Risk factors like middle age obesity, smoking, alcohol consumption, social isolation showed significant association with dementia. Conclusions: Dementia can be prevented by early diagnosis and promoting physical health and treating behavioural and psychological symptoms. Risk of dementia can be reduced by following regular exercise, diet, quitting smoking and alcohol.